Low Energy Water Application (LEWA) device: Concept and applications - SINGH, ATUL KUMAR; ISLAM3, ADLUL; SINGH4, S. R.; UPADHYAYA, ASHUTOSH ,; RAHMAN, A.; SIKKA, A. K. (Journal of Soil and Water Conservation, 2021)
Currently available options in terms of efficient irrigation technologies to the growers in India lacks in technical and economic viability restricting their wide adaptability. Some of the major addressed constraints in this regard have been the majority of the cropping area under field crops, small and fragmented land holdings and limitations of users for high initial investments. This led adoption of these efficient irrigation technologies mostly by large farm holders for crops considered as high valued crop. At the other hand majority of the growers who comes under small and marginal categories still forced to practice surface methods of irrigation which incurs not only huge wastage of water but also the fuel and electric energy used for pumping. Keeping this in view and conditions of small farm holders, an attempt has been made to develop a low cost water and energy efficient device (above canopy). The major focus of the study was to develop a device which can operate at an operating pressure less than 1.0 kg/cm2 at its nozzle head. Reviews indicated that a LEPA nozzle developed by A&M Texas is one of such attempt which operates between 0.07 to 0.35 kg/cm2 operating pressure at nozzle head. Some of the concepts and lessons drawn from LEPA development have been taken into consideration along with the priorities of small holders during this development. This paper discusses the experiences of authors at preliminary stages of development of Low Energy Water Application device (LEWA).